Pitch Lake, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
Photo of railroad bearing a cart loaded with pitch. An employee is seated in front of the cart and in the background at right a few more employees are at work.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Pitch; Railroads--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Asphalt industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; [1910]; Men--Trinidad and Tobago; Employees--Trinidad and Tobago; Working class--Trinidad and Tobago; Blue collar workers--Trinidad and Tobago; Transportation--Trinidad and Tobago; Pitch Lake, The (La Brea)